Vinyl ester/ glass flake nanocomposites: An overview of chemical and physical properties. (June 2014) - Ghadami, Azam; Ehsani, Morteza; Khonakdar, Hossein Ali
The protection of steel against corrosion by nano-glass flake containing coatings has been evaluated in this article. Nano-glass flake was incorporated into epoxy vinyl ester resin by mechanical agitation, homogenizer and sonication process. The dispersion morphology and agglomeration degree of nanoadditives were analyzed by optical microscopy, scanning electron microscopy and energy-dispersive X-ray spectroscopy. The effect of micro and nano-glass flake on anticorrosion performance of epoxy vinyl ester coatings were also compared in a salt spray chamber. The influence of nano-glass flake on the thermal behavior of resins was studied using differential scanning calorimetry and thermogravimetric analysis. The results showed that corrosion resistance of coatings improves as the amounts of nano-glass flake increases to 1.5 phr. Nano-glass-flake-filled specimens display a better corrosion protection than the micro-glass-flake-filled ones.